Alternative sedation for the higher risk endoscopy: a randomized controlled trial of ketamine use in endoscopic retrograde cholangiopancreatography. (October 2015) - Narayanan, Suresh; Shannon, Andrew; Nandalan, Subash; Jaitly, Varun; Greer, Shaun
Abstract Objective. Sedation for endoscopy carries an element of cardiorespiratory risk, more significant for certain procedures and in certain patient groups. Ketamine has features which make it an attractive agent for sedation during the higher risk endoscopy; the objectives of this pilot trial were to assess the effectiveness and tolerability of ketamine as a primary agent for sedation during endoscopy. Methods. The study was a prospective randomized controlled trial, in which American Society of Anesthesiologists' (ASA) class 1–3 patients undergoing endoscopic retrograde cholangiopancreatography (ERCP) received either conventional sedation with midazolam and pethidine or a combination of midazolam and ketamine. Patients were monitored physiologically and in respect to depth of sedation (Modified Observer's Assessment of Alertness/Sedation score) and were observed post procedure for evidence of emergence reactions or other complications. After full recovery, patients completed a questionnaire on their experiences, with particular emphasis on vivid dreaming or other complications attributable to ketamine. Results. Demographically, control (n = 18) and study (n = 19) groups were similar in makeup. Median midazolam dose was 2 mg (interquartile range [IQR] = 1–3) and 2 mg (IQR = 2–3), respectively (p = 0.98); median procedure duration was 25.5 min (IQR = 17–30) and 21.0 min (IQR = 15–34) (p = 0.92). Median satisfaction with sedation (scored from 0 to 4) was 3.5 (range 1–4) and 4 (range 2–4) respectively (p = 0.88). No patient in either group experienced emergence reactions, dysphoria, or vivid dreaming. Conclusion. In this pilot study, sedation for endoscopy with ketamine and midazolam was as effective as conventional sedation, as acceptable to patients, and was not associated with dysphoric events. Ketamine may have potential as an agent for sedation in higher risk patients.